2020
DOI: 10.3390/rs12244174
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Characteristics of Drought Events and Their Effects on Vegetation: A Case Study in Southern Tibet, China

Abstract: Frequent droughts in a warming climate tend to induce the degeneration of vegetation. Quantifying the response of vegetation to variations in drought events is therefore crucial for evaluating the potential impacts of climate change on ecosystems. In this study, the standardized precipitation index (SPI) was calculated using the precipitation data sourced from the China Meteorological Forcing Dataset (CMFD), and then the drought events in southern Tibet from 1982 to 2015 were identified based on the SPI index.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…The most widely used drought indicator is the actual precipitation, represented as a percentage variation from normal (or long-term average), although it has limited use/reliability for regional comparison due to its reliance on the mean [73]. According to Ye et al [74], the SPI reflects a deviation from the mean and is thus expressed as a normalized index in time and space in standard deviation units. The deviation from the mean is a probabilistic indicator of the severity of the wetness or drought that may be used to estimate risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most widely used drought indicator is the actual precipitation, represented as a percentage variation from normal (or long-term average), although it has limited use/reliability for regional comparison due to its reliance on the mean [73]. According to Ye et al [74], the SPI reflects a deviation from the mean and is thus expressed as a normalized index in time and space in standard deviation units. The deviation from the mean is a probabilistic indicator of the severity of the wetness or drought that may be used to estimate risk.…”
Section: Discussionmentioning
confidence: 99%
“…Long records provide more trustworthy statistics for the SPI. As a result of the availability of such data records, the SPI has gained traction as a potential drought indicator in recent years, allowing for comparisons across different precipitation zones [73,74].…”
Section: Discussionmentioning
confidence: 99%
“…By using the "vegan" package, we performed Mantel tests to analyze the relationships between several factors, including rainfall climate, TVDI, NDVI, VSWI, VHI, TCI, and VCI. To determine the relationships between these indices, we divided the R-values and p-values of the Mantel test using the modified function [35]. Finally, to examine the link between these markers, we generated correlation heat maps.…”
Section: Partial Mantel Testmentioning
confidence: 99%
“…The low and negative correlations of some areas may be caused by the complex topographical features and atmospheric conditions. Some studies [68] have shown that the precipitation difference in the Qinghai-Tibet Plateau is the main reason for the north Atlantic oscillation, and the north Atlantic Oscillation and Pacific interannual oscillations has a negative correlation, enhancing the La Niña phenomenon that influenced Indian monsoons. These convective systems and active water vapor transport jets are not alone in creating delays in precipitation and dryness over southern Tibet due to increased water vapor from the Bay of Bengal.…”
Section: Regional Climate Characteristicsmentioning
confidence: 99%